The Conceptualization of Journey in Surah Al-Baqarah: A Cognitive Semantic Study - Septia Khaerunnissa; Fahmy Lukman (Institut Muslim Cendekia, 2026)
This study was motivated by the importance of understanding conceptual metaphors in the Qur’an as a means of representing human experience and constructing abstract meaning. One of the dominant metaphors is the concept of journey, particularly in Surah al-Baqarah, which contains various representations of human spiritual, moral, social, and physical human experiences. This study aimed to analyze the conceptual metaphor of journey in Surah al-Baqarah using a cognitive semantic approach based on Lakoff and Johnson’s Conceptual Metaphor Theory. The study employed a qualitative descriptive method with data collection techniques in the form of documentation and identification of lexicons related to the concept of journey in Surah al-Baqarah. The data were analyzed through source-domain and target-domain mapping to identify conceptual relations and meaning classifications. The findings revealed 23 verses containing seven major lexical forms associated to the concept of journey. These data were then classified into four conceptual domains: spiritual, moral, social, and physical. The analysis showed that the concept of journey in Surah al-Baqarah does not merely refer to physical movement, but also functions as a conceptual framework representing guidance, struggle, responsibility, morality, social solidarity, and divine ease. The novelty of this study lies in its systematic mapping of the concept of journey as a major cognitive structure in Surah al-Baqarah. The findings are expected to contribute to the development of cognitive semantic studies of the Qur’an and provide implications for more contextual and interdisciplinary approaches to Qur’anic interpretation and Islamic studies.